If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-6(x-4)=10
We move all terms to the left:
2-6(x-4)-(10)=0
We add all the numbers together, and all the variables
-6(x-4)-8=0
We multiply parentheses
-6x+24-8=0
We add all the numbers together, and all the variables
-6x+16=0
We move all terms containing x to the left, all other terms to the right
-6x=-16
x=-16/-6
x=2+2/3
| (4x+7)=9 | | 11x=3-(-8) | | 3000=x(.08) | | -17z+18z=-7 | | -3h-4h=-28 | | 7.2=4w | | -7(x+4)-10=22+3 | | 3x+8=x+38 | | 12p-6=198 | | 8d−4=6+6d | | 7x+5+8x=x | | 3-m=-2(m+9) | | m+m+2=22 | | 64+7x=-17 | | 600/57,000=94,000x | | -9z=-6−10z | | -8-6=4x+8-3x | | 5t-9=4t | | 3/4x+1/12x+10=x | | -6f+3=-6f+10 | | (x)=500(1.08)4x | | 4x^2=24-2x^2 | | -7r+9=4-2r | | -5g=-6-6g | | 3+5x+x=180 | | 7s+2=4(s1) | | 2=a/7 | | 7s+2=4(s=1= | | 4/5n-2=2/3n+4 | | -9+10+10w=9w+9 | | 7s+2-(4(s)=0 | | 2x2-28x+6=0 |